USING OF SOFTWARE FOR ESTIMATION OF EXPERT COMPETENCE - Oleg N. Velichko; Tatyana B. Gordienko; Antonina A. Antonina А. Gaber; Pavel F. Baranov (Открытое образование (Москва))
The features of estimation of expert’s competence in the field of higher education are considered, got with a help, both universal statistical software and special software. The comparative analysis of quantitative estimation of expert’s competence is conducted, that showed possibility of forming of the most competent group of experts for realization of necessary group expert estimation in the field of higher education. An analysis showed the high degree of coincidence of results that allow declining less competent experts.